Postgraduate Students’ Common Errors in Writing Education Studies Dissertations: Lessons from the University of Dar es Salaam in Tanzania - Kahangwa , George (University of Dar es Salaam Library Journal, 2024)
The purpose of this study was to investigate common mistakes that postgraduates make in writing dissertation chapters at the University of Dar es Salaam in Tanzania, then propose corrective measures. Using a desk research design, the study reviewed 200 randomly selected master’s degree dissertations. The document review guidelines also facilitated the study’s review of examiners’ reports on the dissertations under review. The information collected was subjected to content analysis. The study found that postgraduate students struggled in stating explicitly the research problems and ended up with vague problem statements. In the limitations section, most of the postgraduates mention trivial issues that the researcher could otherwise address during the planning of logistics. Moreover, the students struggled to critically review literature and, instead, simply described the details or provided summaries of findings from other empirical studies. As a result, the literature review is usually devoid of their respective voices. Students also found difficulties in describing the relationship between the proposed methodology and their study specifically by failing to explain adequately the coherence between the methodology and the nature of the study. Furthermore, some postgraduates failed to analyse data with the required precision; for instance, they use codes and themes interchangeably. Based on the findings, the study recommends intensive and adequate orientation and training of postgraduate students both theoretically and practically on fundamental academic skills for effective writing of quality dissertations.